A study of biogegradable straw from tapioca roots - Hamidon, Nuramidah; Norisman, Nur’Alyaa; Muhamad, Mimi Suliza; Mohd Arish, Nur Aini; A.Hamid, Hazren; Harun, Hasnida; Mohamed Sunar, Norshuhaila; Ali, R.; Tuan Ismail, Tuan Noor Hasanah (Penerbit UTHM, 2020)
Economic development changes people’s lifestyle from various aspect. Statistics shows the world population in 2019 is 7 billion according to World Population Review [1]. The rapid increase of human population has put an incredible strain on our environment. Only 5% of the remaining ocean wilderness is within existing marine protection areas [2]. Kendall Jones who led a research about world’s oceans damaged by human impact are amazed at how little marine wilderness remains. The ocean is immense, covering over 70% of our planet, but almost all of this vast ecosystem have been significantly affected. While developed countries continue to taint the environment and consume its resources, developing countries are under increasing pressure to compete economically and their industrial advancements are damaging as well. Therefore, it can be summarized that as standards of living and disposable incomes increases.